Influence of Ag substitution on the local structure and glass-forming ability of Al86Ni(8-x)Y6Agx (X = 0, 1, 2) liquids. (2nd January 2016) - Liu, Yao; Wang, Jin; Qin, Jingyu; Schumacher, Gerhard
Abstract: The local structure of Al86 Ni(8- x ) Y6 Ag x ( X  = 0, 1, 2) molten and glassy alloy was investigated by ab initio molecular dynamics simulation. It transpired that the Al86 Ni(8- x ) Y6 Ag x alloy can be considered as a combination of Ni- and Y-centred Al clusters with Ag as 'glue atoms'. First and second Ag–Ag coordination was scarcely found in Al86 Ni7 Y6 Ag1, but a medium-range order between 7.5 and 9 Å was observed. The enhanced glass-forming ability and thermal stability of the alloy compared with Al86 Ni8 Y6 can be attributed to the medium-range order of the Ag–Ag correlation. A second Ag–Ag coordination occurs in Al86 Ni6 Y6 Ag2 and results in a decrease in glass-forming ability. The inter-atomic distances between all constituting elements increase during cooling. This increase is ascribed to a change in distribution of clusters around Al atoms towards clusters with higher coordination number around Al.